Free sugars and total fat Are important characteristics of a dietary pattern associated with adiposity across childhood and adolescence - Ambrosini, G; Johns, D; Northstone, K; Emmett, P; Jebb, S (American Society for Nutrition, 2016)
Background The importance of dietary sugar versus fat in the development of obesity is currently a topic of debate. Objective We aimed to identify dietary patterns (DPs) characterized by high sugar and/or high fat content and their longitudinal associations with adiposity during childhood and adolescence. Methods Participants were 6722 children from the Avon Longitudinal Study of Parents and Children (born 1991-92). DPs were characterized by % total energy intake (%E) from free sugars, %E from total fat, dietary energy density (DED) and fiber density, using reduced rank regression at 7, 10 and 13 years of age. Total body fat mass was measured at 11, 13 and 15 years of age. Regression analyses adjusted for dietary misreporting, physical activity and maternal class. Results Two major DPs were identified: higher z scores for DP1 were associated with greater DED, %E from sugars and fat, and lower fiber density; higher z scores for DP2 were associated with greater %E from sugars but lower %E from fat and DED. A 1 SD increase in z score for DP1 was associated with a mean increase in fat mass index z score of 0.04 SD units (95%CI 0.01, 0.07; P=0.017) and greater odds of excess adiposity (OR:1.12, 95%CI: 1.0, 1.25; P=0.038). DP2 was not associated with adiposity. Conclusions An energy-dense DP high in %E from fat and sugars is associated with greater adiposity in childhood and adolescence. This confirms the role of both fat and sugar and provides a basis for food based dietary guidelines to prevent obesity in children.